Activation and modulation of recombinant glycine and GABAA receptors by 4‐halogenated analogues of propofol. (6th September 2016) - Germann, Allison L; Shin, Daniel J; Manion, Brad D; Edge, Christopher J; Smith, Edward H; Franks, Nicholas P; Evers, Alex S; Akk, Gustav
Abstract : Background and Purpose: Glycine receptors are important players in pain perception and movement disorders and therefore important therapeutic targets. Glycine receptors can be modulated by the intravenous anaesthetic propofol (2, 6‐diisopropylphenol). However, the drug is more potent, by at least one order of magnitude, on GABAA receptors. It has been proposed that halogenation of the propofol molecule generates compounds with selective enhancement of glycinergic modulatory properties. Experimental Approach: We synthesized 4‐bromopropofol, 4‐chloropropofol and 4‐fluoropropofol. The direct activating and modulatory effects of these drugs and propofol were compared on recombinant rat glycine and human GABAA receptors expressed in oocytes. Behavioural effects of the compounds were compared in the tadpole loss‐of‐righting assay. Key Results: Concentration–response curves for potentiation of homomeric α1, α2 and α3 glycine receptors were shifted to lower drug concentrations, by 2–10‐fold, for the halogenated compounds. Direct activation by all compounds was minimal with all subtypes of the glycine receptor. The four compounds were essentially equally potent modulators of the α1β3γ2L GABAA receptor with EC50 between 4 and 7 μM. The EC50 for loss‐of‐righting in Xenopus tadpoles, a proxy for loss of consciousness and considered to be mediated by actions on GABAA receptors, ranged from 0.35 to 0.87 μM. Conclusions and Implications: We confirm that halogenation of propofol more strongly affects modulation of homomeric glycine receptors than α1β3γ2L GABAA receptors. However, the effective concentrations of all tested halogenated compounds remained lower for GABAA receptors. We infer that 4‐bromopropofol, 4‐chloropropofol and 4‐fluoropropofol are not selective homomeric glycine receptor modulators.